Uma análise linguístico-discursiva de sujeitos que gaguejam participantes de terapia fonoaudiológica em grupo - Silva, Larissa Petrusk Santos (2013)
There is a broad discussion concerning the studies that ponder the origin and manifestation of the stuttering. Frequently, the studies face stuttering as a manifestation that happens throughout the body: breathing, genetics, heredity and neurological factors. Nowadays, the better known therapeutical proposals follow the principles of the Experimental and Social Psychology, or of the psychoanalysis, of the phenomenological Philosophy, and, specially, from the neurological and genetic biology. The scholars concern themselves about showing a specific spot in the body of the one who stutters or in the survey of the symptoms. In this research, the discourse analysis from the French school, as defended by Pêcheux will be used as theoretical basis. The discourse analysis has for foundation the discourse as structure and event, while "meaning effect between speakers" and suggests the functioning notion. When analyzing the stuttering through this aspect, we propose giving emphasis to the discursive production of the individual who stutters. When stating such idea, it is believed that the stuttering is seen as linguistic-discursive event directly related to the meanings of production of the speaker. The main objectives in this research will be to analyze the linguistic-discursive characteristics of the stuttering in stuttering individuals participants of stuttering speechlanguage pathologic treatment groups, and identify imaginary and discursive formations in the discourse of individuals who stutter. For the discourse analysis on the individuals who stutter, discursive extracts from taped group therapeutical sessions from the Grupo de Estudo e Atendimento à Gagueira (GEAG) in the UNICAP University. The group is constituted of adult individuals who claim voice stuttering, who after a speech-language analysis, are directed to the therapeutical group and, weekly, are reunited with the therapists. The sessions were recorded in audio, and then they were transcribed and analyzed through the discourse analysis point of view. The analysis are made through discursive sequences, and, after the analysis are done, on them the imaginary formations of the individual about himself (as stuttering individual) and of his companions is unveiled. Concepts such as anticipation, silencing, impossibility discourses are manifested in the discourse of the subjects. In the therapeutical proposal of the group, the subjects are leaded to question and the therapist interprets and questions what was spoken, leading the subject to reflect about his own discourse. The dissertation is concluded determining the discursive space as the stuttering space, which is directly related to the subject's means of production. In such process, the need of the reconception of fluency and hesitancy is identified. Through the analysis, the silencing discursive situations were recognized, which are fluency strategies that reassure the individual as stutterer.